Total Knee Arthroplasty after Anterior Cruciate Ligament Reconstruction - Best, Matthew J.; Amin, Raj M.; Raad, Micheal; Kreulen, R. Timothy; Musharbash, Farah; Valaik, Daniel; Wilckens, John H. (The Journal of Knee Surgery, 2020)
The incidence of anterior cruciate ligament (ACL) reconstruction is increasing in the United States, particularly in the older athlete. Patients who undergo ACL reconstruction are at higher risk for undergoing total knee arthroplasty (TKA) later in life. TKA in patients with prior ACL reconstruction has been associated with longer operative time due in-part to difficulty with exposure and retained hardware. Outcomes after TKA in patients with prior ACL reconstruction are not well defined, with some reports showing increased rate of complications and higher risk of reoperation compared with routine primary TKA, but these results are based on small and nonrandomized cohorts. Future research is needed to determine whether graft choice or fixation technique for ACL reconstruction influences outcomes after subsequent TKA. Furthermore, whether outcomes are affected by choice of TKA implant design for patients with prior ACL reconstruction warrants further study. This review analyzes the epidemiology, operative considerations, and outcomes of TKA following ACL reconstruction.
Keywords: anterior cruciate ligament reconstruction; total knee arthroplasty; osteoarthritis